2022
DOI: 10.14218/jcth.2022.00085
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Pancreas: Linking Pancreas Pathophysiology to Nonalcoholic Fatty Liver Disease

Abstract: Currently, scientific interest has focused on fat accumulation outside of subcutaneous adipose tissue. As various imaging modalities are available to quantify fat accumulation in particular organs, fatty pancreas has become an important area of research over the last decade. The pancreas has an essential role in regulating glucose metabolism and insulin secretion by responding to changes in nutrients under various metabolic circumstances. Mounting evidence has revealed that fatty pancreas is linked to impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 100 publications
3
20
0
4
Order By: Relevance
“…Pancreatic fat accumulation has been associated with obesity, impaired b-cell function and may be an early sign in the development of metabolic syndrome (Dite et al 2020, Sequeira et al 2022, Rugivarodom et al 2022). Pancreas is a heterogenous tissue and current tools for fat cell analysis such as Adiposoft (Galarraga et al 2012), AdipoCount (Zhi et al 2018) are unable to analyze fat cell infiltration in pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic fat accumulation has been associated with obesity, impaired b-cell function and may be an early sign in the development of metabolic syndrome (Dite et al 2020, Sequeira et al 2022, Rugivarodom et al 2022). Pancreas is a heterogenous tissue and current tools for fat cell analysis such as Adiposoft (Galarraga et al 2012), AdipoCount (Zhi et al 2018) are unable to analyze fat cell infiltration in pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing literature showed that individuals suffering from chronic pancreatitis have fatter pancreas compared with healthy individuals [40]. Pancreatic steatosis can have adverse effects on metabolism and may play an important role in the development of CVD and metabolic disorders [41], and certain cancers [42]. Concerning the metabolic disturbances, pancreatic adipose tissue has been associated with an increased risk of developing T2DM, and several studies observed higher pancreas adipose tissue accumulation in patients with T2DM compared with normoglycemic individuals, although no associations have been also observed [40].…”
Section: Whole-body Adipose Tissue Distribution and Its Relationship ...mentioning
confidence: 99%
“…Cardiometabolic disorders, particularly obesity and type 2 diabetes mellitus become a global pandemic, affecting 20-30% of the adult population as a consequence of physical inactivity and excessive consumption of the Western diet [1]. These metabolic disorders increased the amount of free fatty acids in the blood, which then accumulated in visceral adipose tissues and other organs including the liver [2,3]. Intrahepatic fat accumulation causes non-alcoholic fatty liver disease (NAFLD), one of the most prevalent chronic liver diseases with a 30% global prevalence [3].…”
Section: Introductionmentioning
confidence: 99%
“…These metabolic disorders increased the amount of free fatty acids in the blood, which then accumulated in visceral adipose tissues and other organs including the liver [2,3]. Intrahepatic fat accumulation causes non-alcoholic fatty liver disease (NAFLD), one of the most prevalent chronic liver diseases with a 30% global prevalence [3]. Through intrahepatic lipotoxicity, NAFLD can progress from simple steatosis to non-alcoholic steatohepatitis (NASH), cirrhosis, hepatic decompensation, and hepatocellular carcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation